THE THREE GOOD THINGS INTERVENTION TO IMPROVE SUBJECTIVE WELL-BEING IN STUDENTS - Fadilah Andriani; Lukman (JIP (Jurnal Intervensi Psikologi), 2023)
ABSTRACT: The pressure from lectures experienced by students can have detrimental effects on their well-being and overall life satisfaction. Therefore, this study aimed to assess the effectiveness of three good things interventions in enhancing the subjective well-being of students. A total of 36 students from Makassar State University participated in this randomized experiment, using an alternative treatment design with a pretest. The Positive and Negative Affect Schedule (PANAS) and Satisfaction With Life Scale (SWLS) were used as measurement tools, and the data were analyzed through an independent sample t-test and analysis of covariance (ANCOVA). The result showed a significant difference in subjective well-being changes between participants who received the three good things intervention and those with a placebo memory, at a t-test significance value of 0.007 and ANCOVA significance of 0.008. Hence, it can be concluded that the three good things interventions positively impact the subjective well-being of students at Makassar State University. This study provided valuable insights on the positive impact of three good things interventions in improving subjective well-being.